Spring stinks - Higgins, Ryan T. (Los Angeles : Disney, Hyperion, 2021)
When cheerful Ruth the rabbit tries to share with grumpy Bruce the bear the wonderful smells of spring, they discover that spring stinks.
Kirkus Review, December 2020
K-3
Keywords: Odors -- Juvenile fiction; Spring -- Juvenile fiction; Bears -- Juvenile fiction; Rabbits -- Juvenile fiction; Odors -- Fiction; Spring -- Fiction; Bears -- Fiction; Rabbits -- Fiction; Humorous fiction